2020
DOI: 10.1521/pedi_2020_34_468
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved Attachment Mediates the Relationship Between Childhood Trauma and Impaired Personality Functioning in Adolescence

Abstract: The present study investigates the mediating effect of attachment trauma on the relationship between childhood maltreatment and personality functioning in 199 adolescents (12-18 years) using a novel approach of an in-depth analysis of attachment-related traumatic contents during an attachment interview (AAP). Our findings demonstrate that adolescents with a high amount of traumatic attachment-related material show a lower resilience when facing traumatic childhood experiences, resulting in a greater severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…As expected, we found a strong significant association between CM experiences and unresolved attachment in mothers. This result is consistent with the results of previous studies using different samples representing various degrees and types of reported maltreatment ( Bakermans-Kranenburg and van IJzendoorn, 2009 ; Buchheim and Diamond, 2018 ; Gander et al, 2018 , 2020 , 2021 ). The prevalence rate in our study cohort with N = 158 participants was 44.9% CM, determined using the recommended cut-off classifications ( Koenig et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…As expected, we found a strong significant association between CM experiences and unresolved attachment in mothers. This result is consistent with the results of previous studies using different samples representing various degrees and types of reported maltreatment ( Bakermans-Kranenburg and van IJzendoorn, 2009 ; Buchheim and Diamond, 2018 ; Gander et al, 2018 , 2020 , 2021 ). The prevalence rate in our study cohort with N = 158 participants was 44.9% CM, determined using the recommended cut-off classifications ( Koenig et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…Gander and colleagues [36]. Concerning the magnitude of the overall relationship between childhood trauma and personality dysfunction, this study demonstrated a strong correlation between the mean scores of the CTQ and LoPF-Q across the entire sample (r = .50) [33]. Examining the specificity of different traumatic effects, emotional trauma (including emotional abuse and neglect) was twice as strongly related to levels of personality dysfunction (r = .51) than physical traumata (including physical abuse, neglect, and sexual abuse; r = .25).…”
Section: Childhood Traumatic Experiences and Personality Functioning (Criterion A)mentioning
confidence: 51%
“…Traumatic emotional abuse may be a form of attachment trauma when it occurs in the context of a primary caregiving relationship (Cyr et al., 2010 ). Childhood emotional abuse also is associated with insecure attachment and identity, intimacy, empathy, and self‐direction problems in adolescence (Gander et al., 2020 ; Goulter et al., 2019 ; Riva Crugnola et al., 2019 ) as well as with adult insecure attachment and dissociation, hopelessness, substance abuse, psychosis, and borderline personality disorder (Frias et al., 2016 ; Goodall et al., 2015 ; Kong et al., 2018 ; Scott et al., 2020 ). Thus, emotional abuse may represent both aspects of trauma exposure in DTD Criterion A (i.e., traumatic victimization and attachment disruption).…”
Section: Discussionmentioning
confidence: 99%